Huanglian Jiedu Decoction in the Treatment of the Traditional Chinese Medicine Syndrome “Shanghuo”–An Intervention Study - Luo, Keke; Zhao, Haiyu; Bian, Baolin; Wei, Xiaolu; Si, Nan; Brantner, Adelheid; Fan, Xiaorui; Gu, Xinru; Zhou, Yanyan; Wang, Hongjie (Frontiers in Pharmacology, 2021)
"Shanghuo" ("excessive internal heat") is caused by exuberant endogenous fire, which does not have a comprehensive and systematic traditional Chinese medicine theory. In previous study, we had evaluated the therapeutic effect of Huanglian Jiedu Decoction (HLJDD) (granule) on patients with "Shanghuo", however, the specific mechanism was not clear, which need further exploration. To explain its intervention mechanism, we select 57 patients with oral diseases caused by "Shanghuo" and 20 health volunteers to divide into oral disease group, HLJDD intervention group and healthy control group. Firstly, biochemical indicators before and after HLJDD intervention are detected, such as inflammatory factors, oxidative stress factors and energy metabolism factors. The results exhibit that HLJDD significantly decreases indicators succinic acid (P < 0.001); tumor necrosis factor-alpha, adenosine triphosphate, citric acid (P < 0.01); interleukin-8 (IL-8), 4-hydroxynonenal, pyruvic acid, lactate dehydrogenase (P < 0.05). The levels of glucocorticoid, adrenocorticotropic hormone (P < 0.01); lactic acid, IL-4, IL-10 (P < 0.05) significantly increase after HLJDD intervention. In addition, we adopt multi-omics analysis approach to investigate the potential biomarkers. Nontargeted metabolomics demonstrate that the levels of 7 differential metabolites approach that in the healthy control group after HLJDD intervention, which are correlated with histidine metabolism, beta-alanine metabolism and sphingolipid metabolism through metabolic pathway analysis. Targeted lipidomics results and receiver operating characteristic curve analysis show that 13 differential lipids are identified in the three groups mainly focuse on lysophosphatidylcholines, lysophosphatidylethanolamines. Finally, the network associations of those differential biomarkers reveal the regulation of adenosine triphosphate and tricarboxylic acid cycle play essential role in the therapeutic effect mechanism of HLJDD in "Shanghuo". The study has laid the foundation for further revealing the mechanism and finding clinical biomarkers related to "Shanghuo".